Pengaruh Harga, Variasi Produk dan Lokasi Terhadap Keputusan Memilih Tempat Hangout (Studi Kasus Pada Wisata Kuliner di Tepian Teratai Kabupaten Berau Kalimantan Timur) - Reynaldi, Agung; Kusdyah Rachmawati, Ike; Handoko, Yunus (Journal of Accounting and Finance Management, 2024)
Tepian Teratai becomes one of the favorite culinary tourism destinations to hangout in Berau District. This is because this district does not yet have a mall or shopping center with limited available famous culinary outlets. Other Tepian also have the same business model, namely a group of street vendors along the banks of the Segah River. However, compared to other Tepians, Tepian Teratai still becomes the favorite choice to hangout. This study aimms to identify and analyze 1) the effect of price on the decision to choose, 2) the effect of product variation on the decision to choose, 3) the effect of location on the decision to choose, and 4) the effect of price, product variation, and location on the decision to choose. This quantitative study used a multiple linear regression analysis technique. The population in this study were visitors to Tepian Teratai, Berau District, East Kalimantan, whose number was unknown / infinite. This study involved 100 respondents as samples selected using a purposive sampling technique. The results of the study showed that 1) price had a positive and significant effect on the decision to choose, 2) product variety had a positive and significant effect on the decision to choose, 3) location had a positive and insignificant effect on the decision to choose, and 4) price, product variety, and location simultaneously had a positive and significant effect on the decision to choose.